Transparency in economic and political decision-making: The identification of sunshine rules for transparent lobbying - Šárka Laboutková; Petr Vymetal (DANUBE: Law, Economics and Social Issues Review, 2017)
Lobbying transparency seems to have been a challenging topic for nearly a decade. For the purposes of the article, the authors focus on a contextual analysis of rules and measures that offers both a broad as well as comprehensive view of the required transparency of lobbying activities and the environment in which decisions are made. In this regard, focusing on the sunshine principles/sunshine rules (not purely limited to laws) provides a grasp of the whole issue in a broader context. From a methodological point of view, the exploratory approach was chosen and the coding procedure is mostly dichotomous. As a result, seven key areas with 70 indicators have been identified in terms of transparency of lobbying and decision-making.
Keywords: 330; Transparency; Lobbying; Decision-Making; Indicator